Storage of nuclear waste suitable for non-invasive monitoring using muon scattering tomography - Mukherjee, Indira; Pallav, Piyush; Roy, Promita; Das, Subhendu; Tripathy, Shridhar; Bhattacharya, Purba; Majumdar, Nayana; Mukhopadhyay, Supratik (EPJ Web of conferences, 2025)
Over the past few decades, research in a form of Non-Destructive Evaluation (NDE), muon tomography, also known as muography, has gained significant attention. In this study, GEANT4 simulations have been used to evaluate the performance of various position-sensitive particle detectors for muography. Detectors with position resolutions ranging from 0 µm (ideal one) to 1000 µm were tested, focusing on developing an imaging algorithm to monitor nuclear waste drums. Additionally, the shape of materials inside nuclear waste drums was analyzed using a Pattern Recognition Method (PRM). The study highlights the importance of storage geometry, track reconstruction and machine-learning algorithms.